Research: A Reliable Way to Reality - Bhattarai, Anjana (Tribhuvan University Journal, 2013)
The word itself tells us that re-search stands for an act of observing something repeatedly in order to find out some new information is research. Highlighting this fact Grinnell (1993) states: The word research is composed of two syllables, re and search. The dictionary defines the former as a prefix meaning again, anew or over again and the latter as a verb meaning to examine closely and carefully, to test and try or to probe. Together they form a noun describing a careful, systematic, patient study and investigation in some field of knowledge undertaken to establish facts or principles. Research is a structured inquiry that utilises acceptable scientific methodology to solve problems and create new knowledge that is generally applicable (as cited in Kumar, 2005:7).